An approach for extending dynamic structural models to multi-product firms - Aviv Nevo; Federico Rossi (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2007)
We propose an approach to extend the standard framework of dynamic games to deal with multi-product firms. Our approach applies to industries with a large number of products offered by a small number of firms.
Keywords: 330; Mehrproduktproduktion; Dynamisches Spiel